Optimizing Organizational Commitment - Puspita Dewi, Sari; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
This research aims to determine the influence of human resource development and work quality on organizational commitment with work strategy as an intervening variable at the Bpjs Jambi City Branch. This research uses quantitative, primary data as well as a data source. The collection technique used is by distributing questionnaires to respondents and the population. Used were 60 employees, the sample used was the entire population because it used a saturated sampling technique. The results of this research are as follows, Work Quality has a positive and significant effect on Organizational Commitment with an original sample value of 0.070 and ap value of 0.362, Work Quality has a positive and significant effect on Work Strategy with an original sample of 0.462 and ap value of 0.000, HR Development has a positive and significant effect on Organizational Commitment with the original sample of 0.371 and p value 0.014. HR development has a positive and significant effect on Work Strategy with an original sample value of 0.440 and ap value of 0.000. Work Strategy has a positive and significant effect on Organizational Commitment with an original sample value of 0.380 and ap value of 0.012. Work Quality has a positive and significant effect on Organizational Commitment through Work Strategy with an original sample value of 0.175 and ap value of 0.035. HR development has a positive and significant effect on Organizational Commitment through Work Strategy with an original sample value of 0.167 and ap value of 0.029.